Causal association between constipation and risk of colorectal cancer: a bidirectional two-sample Mendelian randomization study - Wu, Long; Wu, Huan; Huang, Fei; Li, Xiao-yun; Zhen, Yun-huan; Zhang, Bao-fang; Li, Hai-yang (Frontiers in Oncology, 2023)
Background: Colorectal cancer (CRC) is a globally significant health concern, necessitating effective preventive strategies through identifying modifiable risk factors. Constipation, characterized by infrequent bowel movements or difficulty passing stools, has been proposed as a potential CRC risk factor. However, establishing causal links between constipation and CRC remains challenging due to observational study limitations.Methods: Mendelian randomization (MR) utilizes genetic variants as instrumental variables, capitalizing on genetically determined variation to assess causal relationships. In this dual-sample bidirectional MR study, we extracted genetic data from independent cohorts with CRC (Include colon cancer and rectal cancer) and constipation cases. Genome-wide association studies (GWAS) identified constipation and CRC-associated genetic variants used as instruments to infer causality. The bidirectional MR analysis evaluated constipation's impact on CRC risk and the possibility of reverse causation.Employing bidirectional MR, we explored the causal relationship between constipation and CRC using publicly available GWAS data. Analysis of constipation's effect on CRC identified 26 significant SNPs, all with strong instrumental validity. IVW-random effect analysis suggested a potential causal link [OR = 1.002(1.000, 1.004); P = 0.023], although alternative MR approaches were inconclusive. Investigating CRC's impact on constipation, 28 significant SNPs were identified, yet IVW analyses found no causal effect [OR = 0.137(0.007, 2.824); P = 0.198]. Other MR methods also yielded no significant causal association. We analyzed constipation separately from colon and rectal cancer using the same methodology in both directions, and no causal relationship was obtained.Our bidirectional MR study suggests a potential constipation-CRC link, with mixed MR approach outcomes. Limited evidence supports constipation causing CRC. Reliable instruments, minimal heterogeneity, and robust analyses bolster these findings, enriching understanding. Future research should explore additional factors to enhance comprehension and clinical implications.